Syncing with the Sky: Daylight-Driven Circadian Lighting Design. Issue 3 (3rd July 2021) - Altenberg Vaz, Nathan; Inanici, Mehlika
ABSTRACT: The use of daylight in the built environment is often preferred to artificial light sources as its successful application can provide visual comfort and satisfaction along with the potential for significant energy savings. Exposure to daylight is also the primary source for stimulus that establishes a healthy day/night cycle in all living organisms. This is known as circadian rhythm. Newly discovered photoreceptors (intrinsically photosensitive retinal ganglion cells – ipRGC) within the mammalian eye, including humans, are specifically linked to the portion of the brain responsible for maintaining a healthy circadian rhythm. This discovery has led to a new subject area in the field of lighting design focused on controlling the spectrum of light that these photoreceptors are sensitive to. Currently, work in the field of circadian lighting design is concentrated on the use of artificial light sources for circadian stimulus. This is largely due to the advent of the widespread use of LED technology, which has proven that it can be a significant source of light that can delay or advance the circadian clock. The use of daylight to provide circadian stimulus has been a given in this field of design, however, there has not been very much research into how the built environment affects our ability to effectively receive this stimulus from daylight. In this research, the groundwork is established to start to create a set of guidelines to help architects and designers maximize the potential for daylight to provide circadian stimulus at the earliest stages of a project. This is accomplished through a series of lighting simulations that explore and test various architectural parameters that affect daylight-driven circadian lighting, with simultaneous consideration given to photopic lighting availability and visual comfort. The architectural parameters tested in this study included window head height, building orientation, shading devices, visual obstructions to the sky, and room depth. The results show that informed design decisions could maximize circadian potential in a given space, while achieving visually satisfactory luminous environments.